2016
DOI: 10.20463/jenb.2016.03.20.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute interval sprinting exercise on postprandial lipemia of sedentary young men

Abstract: [Purpose]Postprandial lipemia (PPL) contributesto the development of atherosclerosis. In females, repeated 8-second bouts of interval sprinting exercise reduced PPL, however, the effect of 8-second bouts of interval sprinting on PPL of overweight males is undetermined. Thus, the effect of 8-secondsof interval sprinting for 20 min, the night before ingestion of a high-fat meal (HFM), on plasma triacylglycerol(TG) levelswas examined.[Methods]Ten overweight males acted as participants (BMI = 26±3.0kg/m2, age 22 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…With regard to postprandial endothelial function, evidence has shown that a single bout of exercise prior to HFM consumption improves fasting and postprandial endothelial function compared with a resting control condition [ 11 13 ]. Accordingly, it has been reported that acute moderate- and high-intensity exercise has transient benefits for macrovascular endothelial function in both fasting and postprandial states, and that these effects may be due to the improvement in antioxidant status [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to postprandial endothelial function, evidence has shown that a single bout of exercise prior to HFM consumption improves fasting and postprandial endothelial function compared with a resting control condition [ 11 13 ]. Accordingly, it has been reported that acute moderate- and high-intensity exercise has transient benefits for macrovascular endothelial function in both fasting and postprandial states, and that these effects may be due to the improvement in antioxidant status [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, 36 studies have confirmed that exercise performed on the evening prior to a morning high-fat meal (that is, a meal containing above 0.7 g of fat per kg body mass) lowers PPL, compared to no exercise. This has been shown in young, middle-aged and/or older men [14,21,[33][34][35][36][37][38][39][40][41][42]22,43,76,77,23,[27][28][29][30][31][32], young men and women [44], young or middle-aged women [45,67], normal and overweight individuals [68], overweight and obese individuals [24,46,47] and adolescent boys and girls [48][49][50][51][52][53].…”
Section: Exercise Performed On the Day Preceding A High-fat Mealmentioning
confidence: 84%
“…To document this, we examined how many of the original studies that are included in the present review and showed a significant effect of exercise on PPL satisfied the criterion of lowering circulating TAG by at least 1 mmo/L, which is the minimal established clinically relevant effect [15,16]. On this basis, 7 studies demonstrated a clinically relevant effect, with an average TAG reduction of 38 % (range 29 to 47 %) [21][22][23][24][25][26][27], whereas 42 studies did not find a clinically relevant effect, with an average TAG reduction of 22 % (range 4 to 35 %) [14,. iv.…”
Section: Why Is Exercise Important In Lowering Ppl?mentioning
confidence: 99%
“…The average energy expenditure in the EX group was approximately 370 kcal. This level of energy expenditure has recently been shown to reduce PPL in sedentary overweight men (Chu et al 2016). In fact, the researchers report that exercise duration of only 20 minutes at 60% power elicited a 20% reduction in PPL.…”
Section: Discussionmentioning
confidence: 99%